DAMPAK INVESTASI DAN KONSUMSI TERHADAP PERTUMBUHAN EKONOMI INDONESIA: PENDEKATAN ANALISIS ERROR CORECTION MODEL - Busra Busra; Yuli Anisah (Ekonis: Jurnal Ekonomi dan Bisnis, 2019)
Abstrack: This study aims to analyze the impact of investment and consumption on Indonesia's economic growth. this study uses data sourced from the Indonesian Central Bureau of Statistics from 1960 - 2014, with 54 years of data. the data used are data on economic growth, consumption and investment data during this period. all data were tested by unit root test and cointegration, and statistics and cointegration at first difference. Next. using the error correction model approach, we find that investment and consumption adjust economic growth in 1 (one) lag. The influence of the Investment Fund on economic growth can be seen in the short term. This shows that the Investment variable has a significant relationship. towards Economic Growth. Keywords: Error corection model, investation, consumption, first difference, cointegrasi